Determining Risk Factors of Bleeding in Patients on Warfarin Treatment - Evren Uygungül; Cuneyt Ayrik; Huseyin Narci; Semra Erdoğan; İbrahim Toker; Filiz Demir; Ulas Karaaslan (Advances in Hematology)
Background. Warfarin is a commonly used oral anticoagulant agent. The most common adverse effects of warfarin are bleeding complications. Methods. We performed a 1-year retrospective chart review of emergency department patients using warfarin. A total of 65 patients with bleeding disorder (study group) and 63 patients without bleeding (control group) were included, making up a total of 128 subjects. Demographic data, frequency of international normalized ratio (INR) checks, and routine blood results were extracted. Logistic regression analysis was used to determine which factors were most closely associated with bleeding complications. Results. Median age was 62.0±14.4 and 61.9±14.5 for study group and control group, respectively. Educational status and frequency of INR checks were similar in both groups (P=0.101 and P=0.483, resp.). INR levels were higher in the study group (5.45±3.98 versus 2.63±1.71, P<0.001). Creatinine levels were also higher in the study group (1.14±0.57 mg/dL versus 0.94±0.38 mg/dL, P=0.042). Acetylsalicylic acid use was more frequent in the study group and was associated with a 9-fold increase in bleeding complications (P<0.001). Conclusions. High INR levels, high creatinine levels, and acetylsalicylic acid use were associated with bleeding complications in ED patients using warfarin.